Maternal anemia and red blood cell requirements in 72 women undergoing ex-utero intrapartum treatment (EXIT) procedure - Kloka, Jan Andreas; Jasny, Thomas; Jennewein, Lukas; Friedrichson, Benjamin; Zacharowski, Kai; Neef, Vanessa (Frontiers in Medicine, 2024)
Background The ex-utero intrapartum treatment (EXIT) allows to ensure fetal airway while keeping uteroplacental circulation. However, EXIT may become a life-threatening procedure due to the increased risk of uterine atony or placenta abruption with increased peripartum blood losses and increased transfusion rates. We aim to review maternal anemia prevalence and transfusion requirements in women undergoing EXIT procedure. Methods Using data from the Federal German Statistical Office hospitalized women undergoing EXIT procedure between January 1st 2006 and December 31st 2021 were included. The prevalence of anemia, peripartum hemorrhage, comorbidities and administration of red blood cells (RBC) were analyzed. Results In total, 72 women underwent EXIT procedure with a median age of 31 years (26;33.5). In 43.1% EXIT was conducted at 34–36 weeks of gestational age. “Anemia during pregnancy” was present in 47.2%, “anemia due to acute bleeding” in 25.0% and “iron deficiency anemia” in 15.3%. Postpartum hemorrhage occurred in 11.1%. RBCs were transfused in 15.3% of all women. Most women required 1–5 units of RBCs. Conclusion Despite the rarity of this procedure, anemia management and blood conservation strategies in order to reduce the need for RBC transfusion are highly important in women undergoing EXIT procedure.